Historic buildings of the Warsaw University of Technology - selected issues of renovation, modernisation and adaptation = Zabytkowy zespół gmachów Politechniki Warszawskiej - wybrane zagadnienia związane z renowacją, modernizacją i rozbudową - Wagner, Anna Agata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The historic buildings of the Warsaw University of Technology display not only outstanding architectural values, but are also representative of the trends in preservation, restoration, and adaptation that were prevalent at the time of their modernization. The post-war rebuilding of the WUT was more akin to modernization than reconstruction.
Keywords: Politechnika Warszawska; budynki zabytkowe; modernizacja; adaptacja; renowacja; Warsaw University of Technology; historic building; modernisation; adaptation; renovation